The 19th National Assembly Election and Post-Election Political Changes in Korea - Turtogtokh Janar (Politology, 2023)
In this paper, the author will not examine whole issues of parliamentary institutions, but examine some aspects of Korea’s legislature. At the beginning, this work covers historical and constitutional basis of the National Assembly of the Republic of Korea (ROK). Then it shows the National Assembly as a national law-making body as well as a political representative institution. In the field of parliamentary institutional research, the study of the electoral system and its realization is of the utmost importance. Therefore, this paper covers the issues on election system for a legislative institution, and its effect on the country’s political process. Next part is about 19th Assembly election results and political parties of Korea, and election results implications for the presidential elections of Korea. Last but not least, Korean women’s political achievements are discussed.